Passivity Based Control of Four-Switch Buck-Boost DC-DC Converter without Operation Mode Detection - Komurcugil, Hasan; Bayhan, Sertac; Guler, Naki; Guzman, Ramon (IEEE, 2022)
This paper presents a passivity-based control approach for four-switch buck-boost (FSBB) DC-DC converters. The state variables are selected as the inductor current and the capacitor voltage errors. The passivity based control is formulated that targets to drive the inductor current and capacitor voltage to their reference values. The reference of the inductor current is produced by a proportional-integral controller that operates on the capacitor voltage error. Two control input equations are defined for buck and boost operations due to the fact that FSBB converter contains separate switches for buck and boost stages. As a consequence of controlling each stage by the dedicated control input, the passivity based control method eliminates the need for using a mode detection algorithm. The validity and superiority of the proposed approach has been studied by Matlab/Simulink simulations under load step, reference voltage step and operation mode variations for buck and boost modes. The results reveal that the proposed control approach can regulate the output voltage under all cases.
48th Conference of the Industrial Electronics Society-IECON-Annual -- OCT 17-20, 2022 -- Brussels, BELGIUM
Keywords: Four switch buck-boost converter; duty cycle; voltage regulation; current control; passivity based control